2021
DOI: 10.1007/s00068-021-01773-2
|View full text |Cite
|
Sign up to set email alerts
|

Does 3D-assisted surgery of tibial plateau fractures improve surgical and patient outcome? A systematic review of 1074 patients

Abstract: Purpose The aim of this systematic review was to provide an overview of current applications of 3D technologies in surgical management of tibial plateau fractures and to assess whether 3D-assisted surgery results in improved clinical outcome as compared to surgery based on conventional imaging modalities. Methods A literature search was performed in Pubmed and Embase for articles reporting on the use of 3D techniques in operative management of tibial plate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 41 publications
1
29
0
Order By: Relevance
“…The results of the present review are consistent with existing literature; when investigating its use in acetabular fractures, a recent systematic review identified that 3D printing for pre-operative planning significantly improved surgery in terms of surgical time, blood loss, quality of reduction and clinical outcomes [23]. These results are echoed in further reviews exploring various fracture types [26,28,29,39].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The results of the present review are consistent with existing literature; when investigating its use in acetabular fractures, a recent systematic review identified that 3D printing for pre-operative planning significantly improved surgery in terms of surgical time, blood loss, quality of reduction and clinical outcomes [23]. These results are echoed in further reviews exploring various fracture types [26,28,29,39].…”
Section: Discussionsupporting
confidence: 87%
“…Increasing interest in 3D printing-assisted surgery has been accompanied by mounting evidence pointing towards its efficacy in pre-operative planning, with promising results being presented in the research of various musculoskeletal injuries [20][21][22], though much of this research has focussed on acetabular and tibial plateau fractures [23][24][25][26][27]. Existing reviews have investigated 3D printing-assisted surgery in calcaneal and pilon fractures in isolation [28,29], however, the aim of this systematic review was to determine the efficacy of 3D printing in the pre-operative planning of combined foot and ankle fractures.…”
Section: Introductionmentioning
confidence: 99%
“…They thought that the 3D‐printed model was useful for communication with patients. Other reports 12–14 showed that the operation time, blood loss, and number of intra‐operative fluoroscopy for the 3D printing group exhibited statistically significant differences compared with the traditional surgery group in TPFs. A recent review 12 showed that a 3D‐assisted surgery resulted in reduced operation time (104.7 vs 126.4 min; p < 0.01), less blood loss (241 ml vs 306 ml; p < 0.01), and decreased frequency of fluoroscopy (5.8 vs 9.1 times; p < 0.01) in TPF.…”
Section: Discussionmentioning
confidence: 91%
“…Previous reviews have focused on the description and technical details of the involved steps (Jiménez-Delgado et al, 2016) or on a specific type of fracture treatment, such as acetabular fracture surgery (Boudissa et al, 2018). Banierink et al (2021) and Assink et al (2021) have both reviewed whether '3D-assisted surgery' improves clinical outcomes when used for the planning of pelvic ring fractures and tibial plateau fractures, respectively. However, these reviews focus on different concepts of 3D-assisted surgery, including 3D virtual visualization, 3D printed hand-held fracture models, pre-contouring of osteosynthesis plates, 3D printed surgical guides, and intra-operative 3D imaging, rather than computer models to assist in planning.…”
Section: Rationalementioning
confidence: 99%